2021
DOI: 10.1136/archdischild-2021-321792
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic on routine childhood immunisation in Colombia

Abstract: ObjectiveTo assess the impact of the COVID-19 pandemic on routine childhood vaccination coverage in Colombia by age group, rural/urban residence, state and vaccine type.DesignEcological study of official monthly vaccination records.SettingVaccination records from the Colombian Ministry of Health (March–October 2019 and 2020).ParticipantsAggregated data for Colombian children (<12 months, n=676 153; 12–23 months, n=700 319; and 5 years, n=734 295) participating in the Expanded Program on Immunization.Main ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 27 publications
4
46
1
3
Order By: Relevance
“…The leading causes of under 5-year-old children morbidity in Ethiopia,25 including acute respiratory illness, fever and diarrhoea, may have decreased due to school closures (older siblings less exposed), limited interactions with peers in the community, spending more time indoors, mask-wearing at community gatherings, hand washing, physical distancing, and other PPE and practices. Despite a marked reduction in supply chain distribution of vaccines in Ethiopia during COVID-19,26 we found that RI remained stable during the initial 6 months of the pandemic, which was different from the findings in Colombia, India, and Brazil where RI declined during the pandemic 27–29. The MOH of Ethiopia prioritised RI, especially measles, during COVID-19.…”
Section: Discussioncontrasting
confidence: 92%
“…The leading causes of under 5-year-old children morbidity in Ethiopia,25 including acute respiratory illness, fever and diarrhoea, may have decreased due to school closures (older siblings less exposed), limited interactions with peers in the community, spending more time indoors, mask-wearing at community gatherings, hand washing, physical distancing, and other PPE and practices. Despite a marked reduction in supply chain distribution of vaccines in Ethiopia during COVID-19,26 we found that RI remained stable during the initial 6 months of the pandemic, which was different from the findings in Colombia, India, and Brazil where RI declined during the pandemic 27–29. The MOH of Ethiopia prioritised RI, especially measles, during COVID-19.…”
Section: Discussioncontrasting
confidence: 92%
“…In summary, although two moderate risk-of-bias studies [20,22] failed to show evidence of increasing inequity during the pandemic, three low-risk-of-bias studies [14,21,23] report moderately strong evidence of increasing inequity, with additional, but weak, supporting evidence from Bramer et al [24].…”
Section: Outcome 1: Change In Routine Childhood Vaccination Coverage ...mentioning
confidence: 83%
“…This could be attributed to the probably higher caregivers' concerns about exposing their vulnerable newborns and other children under the age of 12 months to the risk of COVID-19. This age-related difference in vaccination coverage during the pandemic was also documented in Colombia where the highest decline in vaccination coverage during March-October 2020 was observed in children under the age of 12 months, in particular those living in rural areas [ 20 ]. Similarly, in Michigan, around 17% reduction in the percentage of vaccinated children at the age of 5 months was documented in May 2020 as compared to around 10% and 5% reduction at ages of 19 months and 24 months, respectively [ 4 ].…”
Section: Discussionmentioning
confidence: 67%